PENGARUH KEMAMPUAN TEKNIK PERSONAL, KETERLIBATAN PEMAKAI DAN INFOMATION TECHNOLOGY SOPHISTICATION TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI DI BPR KABUPATEN GIANYAR - Ni Putu Cantik Lediana Putri; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2020)
Accounting information system performance is a description of the level of achievement during using accounting information systems in a certain period, the purpose of this study is to determine thel effect of personal engineering abilities, user involvement, and information technology sophistication on the performance of accounting information systems. The population in this study are all employees who work at BPR ls located in Gianyar Regency. The sampling method used in this study is the non probability sampling method with a purposive sampling technique which is a sampling technique by determining certain criteria or considerations. Respondents in this study were 127 respondents. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of this study indicate that the ability of personal techniques has a positive and significant effect on the performance of accounting information systems, user involvement has a positive and significant effect on the performance of accounting information systems, and information technology sophistication has a positive and significant effect on the performance of accounting information systems on BPR in Gianyar Regency.